Assessment of Groundwater Quality Using Water Quality Index from Selected Springs in Manga Subcounty, Nyamira County, Kenya - Alice Makonjo Wekesa; Calford Otieno (The Scientific World Journal)
We present the results of groundwater quality assessment that was done during the rainy season in November 2018 in the Manga region of Nyamira County, Kenya. Water samples were collected from three springs, Kiangoso, Kerongo, and Tetema, for the assessment. Water quality index was calculated based on pH, turbidity, nitrate, phosphate, calcium, magnesium, chloride, sulphates, fluoride, iron, total phosphorous, total hardness, total alkalinity, total dissolved solids, and total coliform. These fifteen parameters were analyzed and characterized according to standard methods and with reference to the World Health Organization and Kenya Bureau of Standards for physiochemical and bacteriological parameters which were then used in the calculation of water quality index. The water quality index was 21.32 for Kiangoso, 29.66 for Kerongo, and 25.64 for Tetema. The water quality index was found to be of excellent quality status at Kiangoso, while of good quality status at Kerongo and Tetema. The water quality index of Manga groundwater represented by the three springs therefore is less than 30 and can be used for drinking, irrigation, and industrial purpose. The present results are crucial for future management of groundwater in the Manga region.